Anemia prevalence and the knowledge, attitute and behaviour towards anemia in pregnant women living in Abdullahpaşa Education and Research Health Center region - Polat, S. Aytaç; Tevfik Ozan, A.; Açik, Yasemin; Güngör, Yüksel (My University, 2001)
The aim of this study was to determine the anemia prevalance and the knowledge level and attitute of pregnant women living in Abdullahpaşa Education and Research Health Center. This study was performed between March and April 2001, data were obtained from questionary form and from record of the Health Center about 123 pregnant women. The mean age of the subjects included in this study was 26.1 years, 39.3% was in age range of 20-24 years, of the subjects 50.9% was primary school graduate, 94.6% was housewife, 15.2% had no social security and 59.8% had less than 200 million TL monthly income. In 43.8% of the pregnant subjects the haemoglobin level was ?11g/dl. 65.3% of the patients with anemia was in in third trimester while 40.8% was in the second trimester of the pregnancy. In 71.4% of the patients it was reported that they have had tea and/or coffee after meals, 91.8% was non-smoker, 26.5% was changed the normal feeding habits after they became pregnant. The first three food preferred by the pregnants were milk (43.8%), fruit 32.1%) and vegetables (30.4%), respectively. Of the patients 63.4% was considered the anemia as important health problem, the reason of anemia was thought to be due to multiple birth by 79.5%, to intestinal parasites in 34.8%, and 36.6% was thought that anemia causes tiredness in pregnancy. In 12.5% of the subjects it was thought that the pregnancy interval should be at least 24 months for prevention from anemia. The results of this study indicate that the anemia prevalence was high in the subjects involved in this study and the knowledge level about anemia was low. In conclusion: informative and educational services should be provided and in pregnants with diagnosed anemia medical intervention should be performed.
Abdullahpaşa E?itim ve Araştirma Sa?lik Oca?i bölgesinde yaşayan gebelerde anemi prevalansi ve gebelerin anemi konusundaki bilgi, tutum ve davranişlari
Keywords: Anemia; Feeding; Pregnancy